KONTROL RIPPLE SUPPRESSION PADA LOW-INDUCTANCE BUCK CONVERTER UNTUK CONTINUOUS CONDUCTION OPERATION - Fifi Hesty Sholihah (SMARTICS Journal, 2025)
This work proposes a control strategy that keeps a buck converter in Continuous Conduction Mode (CCM) even with a low inductance. The architecture is a cascaded scheme with an outer voltage loop and an inner current loop featuring a valley clamp to prevent inductor-current collapse, complemented by feedforward and anti-windup under duty saturation. The approach is validated in simulation across inductances L=L=L= 40 mH, 10 mH, 5 mH, and 1 mH, and under both resistive and inductive (R–L) loads. Results show consistent suppression of current and voltage ripple. At L=1 mH, inductor-current ripple decreases from 12.44 Ap−p to 1.918 Ap−p ​ (≈6.5×), while output-voltage ripple drops from 8.536 V to 0.63 V (≈13.6×), with the output regulated at 60 V. At L=10 mH, current ripple is reduced from 1.748 A to 0.337 A (≈5.2×) and voltage ripple from 4.855 V to 0.11 V (≈44×). The controller also damps R–L load effects so the inductor current never hits zero. These findings indicate that low-inductance operation is feasible while preserving power quality, stability, and enabling higher power density